Pemberian Urine Sapi dan Penentuan Dosis Pupuk N Pada Tanaman Ketimun (Cucumis Sativus, L.) - Widyastuti, Titiek; Wijaya, Insan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
An experiment to study the effect of cow urine applications and dosage of N fertilizer was conducted in Bondowoso, from February to April 2002. A factorial experiment consisted of two factors and the whole treatments were arranged in 3x4 factorial Randomized Complete Block Design (RCBD) with 3 replications. The first factor was urine of Cow, consist of U0 = control, U1= 20%, U = 40%. The second factor was dosage of N fertilizer, consist of N1 = 0 kg/ha, N2 = 150 kg/ha, N3 = 300 kg/ha, N4 = 450 kg/ha. The effect of treatments on growth and yield of cucumber were observed. The result showed that there was no interaction between cow urine application and dosage of N fertilizer, except to the fruit diameter. Cow urine application significantly improved the yield of Cucumber, and the 40% application gave the best fruits weight. Dosage of N fertilizer significantly increased the growth and yield of cucumber, and the 450 kg N-fertilizer/ha had the better effects.